Based of Facts on How Automobile Industries Handle Their Recall System : A Case Study - Abigael Brilliana Christanti; Christopher Suputro; Liem Gai Sin (Journal of International Conference Proceedings (JICP), 2018)
This paper examines about many research, studies and facts of some automobiles industries in term of their recall system. Automobile industry recalled their product from the customers in case of imperfect or massive malfunction. The paper collects many recall history around the world to compare and giving correct, proper and effective system of recall. This research is descriptive research which analysis is done based on studies, online news and reports. The outcome of this research is analyzing the important factors that determine success of automobile recall. Keywords – Automobile Industry, History, Recall System, Service